2005
DOI: 10.1016/j.cmet.2005.08.004
|View full text |Cite
|
Sign up to set email alerts
|

FoxO1 protects against pancreatic β cell failure through NeuroD and MafA induction

Abstract: Diabetes causes pancreatic beta cell failure through hyperglycemia-induced oxidative stress, or "glucose toxicity." We show that the forkhead protein FoxO1 protects beta cells against oxidative stress by forming a complex with the promyelocytic leukemia protein Pml and the NAD-dependent deacetylase Sirt1 to activate expression of NeuroD and MafA, two Insulin2 (Ins2) gene transcription factors. Using acetylation-defective and acetylation-mimicking mutants, we demonstrate that acetylation targets FoxO1 to Pml an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

43
502
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 524 publications
(571 citation statements)
references
References 56 publications
43
502
4
Order By: Relevance
“…These data suggest that FOXO1 may have a significant role in inhibiting beta cell differentiation during human fetal pancreatic development. FOXO1 presence in the nucleus has been shown to be indicative of biological activity [9]. Our immunohistochemical analyses demonstrated relatively constant levels of nFOXO1 in both ductal and islet cell populations of the 8-21 week human fetal pancreas.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…These data suggest that FOXO1 may have a significant role in inhibiting beta cell differentiation during human fetal pancreatic development. FOXO1 presence in the nucleus has been shown to be indicative of biological activity [9]. Our immunohistochemical analyses demonstrated relatively constant levels of nFOXO1 in both ductal and islet cell populations of the 8-21 week human fetal pancreas.…”
Section: Discussionmentioning
confidence: 49%
“…This differential nuclear vs cytoplasmic localisation of FOXO1 and PDX-1 has been shown in HIT-T15 cells to work through the c-Jun N-terminal kinase pathway [8]. The presumption that FOXO1 protects against beta cell failure has been further supported by studies demonstrating its ability to increase neurogenic differentiation 1 (NEUROD) and v-maf musculoaponeurotic fibrosarcoma oncogene homologue A (MAFA) production, a compensatory response that preserves beta cell function under metabolic stress conditions [9].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast, FOXO1-3KA and FOXO1-3KQ mutants of the same lysine residues have less DNA-binding affinity. Similarly, Kitamura et al (2005) found that FOXO1-6KR mutant (mimicking deacetylated form of FOXO1) has better DNA-binding affinity and stronger transactivation of a FOXO luciferase reporter than the 6KQ mutant (K242R, K245R, K259R, K262R, K271R and K291R), which mimicks acetylated form of FOXO1. We have also found that SIRT2 increases FOXO3 binding to p27 promoter region by chromatin immunoprecipitation assay (Wang et al, 2007).…”
Section: Discussionmentioning
confidence: 90%
“…Published evidence suggests that SirT1 prevents ageassociated diseases such as metabolic disorders (Picard et al, 2004;Kitamura et al, 2005;Moynihan et al, 2005;Bordone et al, 2006;Gerhart-Hines et al, 2007;Rodgers and Puigserver, 2007), neurodegenerative diseases (Araki et al, 2004;Parker et al, 2005;Chen et al, 2005a;Qin et al, 2006;Kim et al, 2007) and atherosclerosis . Accumulating evidence also point to SirT1 as having a function in cancer; however, inferences from the literature are that SirT1 has both oncogenic and tumor-suppressor activities.…”
Section: Introductionmentioning
confidence: 99%